Prebiotic, Probiotic, and Synbiotic Effect on Performance and Small Intestinal Morphology of Broiler Chicken - Assaf, A. F.; Rahardja, D.P.; Purwanti, S. (Hasanuddin Journal of Animal Science (HAJAS), 2025)
The study was conducted to investigate the effect of prebiotic, probiotic, and synbiotic supplementation through drinking water on broiler performance and small intestine morphology. A total of 100 day-old broiler chicks (Ross) were randomly allocated into 4 treatments with 5 replicates, with 5 broilers in each experimental unit for 35 days. The drinking water treatments were P0: Water (Control); P1: Water + Prebiotic (5 g/L); P2: Water + Probiotic (3 g/L); P3: Water + Synbiotic (Probiotic 3 g/L + prebiotic 5 g/L). Commercial feed consisting of the three rearing phases was used during the study, and drinking water was provided ad libitum. Parameters measured were water and feed consumption, body weight gain, feed conversion, performance index, small intestine morphometry, which is measured by the length/weight ratio, and Histo-morphometry of the small intestine of individual segments, duodenum, jejunum, and ileum at the end of the experiment on 3 chicken samples (lightest, medium, heavy) from each treatment. The results showed that prebiotic, probiotic, and synbiotic supplementation through drinking water significantly (P<0.05) affected drinking water and feed consumption, body weight gain, feed conversion, length/weight ratio, and histo-morphology of the small intestine. Overall, it can be concluded that synbiotic supplementation demonstrated a synergistic effect between prebiotics and probiotics, outperforming prebiotic and probiotic supplementation separately in terms of performance, small intestine ratio, and small intestine histomorphology. Synbiotics also significantly showed a trend towards feed use efficiency, as seen in feed conversion. Keywords: Broiler Chicken, Natural Growth Promotor, Performance Index, Intestinal Gut Ratio, and Intestinal Histomorphometry